1981
DOI: 10.1111/j.1365-2923.1981.tb02500.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of house-physicians towards self-poisoning patients

Abstract: Eighty-two house-physicians filled in a questionnaire concerning the care of self-poisoning patients with special emphasis on training and attitudes. These recently qualified doctors dealt with large numbers of such patients and expressed dissatisfaction with their training in this respect. Hostile attitudes towards these patients developed most clearly at those district hospitals where psychiatrists are rarely available. During their 6 months as a house-physician, doctors at the teaching hospital became more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
1

Year Published

1984
1984
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 11 publications
3
12
1
Order By: Relevance
“…[69][70][71][72][73][74] Similar negative attitudes are also found in the psychiatric services. 75 Self harmers suVer from the stigma of psychiatric problems, and they are often seen as undeserving and detracting from the clinical care of others whose illnesses are not perceived as self inflicted.…”
Section: Psychosocial Assessmentmentioning
confidence: 68%
“…[69][70][71][72][73][74] Similar negative attitudes are also found in the psychiatric services. 75 Self harmers suVer from the stigma of psychiatric problems, and they are often seen as undeserving and detracting from the clinical care of others whose illnesses are not perceived as self inflicted.…”
Section: Psychosocial Assessmentmentioning
confidence: 68%
“…In a study by Creed and Pfeffer, the results showed more positive attitudes among physicians towards somatic diagnoses than self harm [25]. There is no available validated scale for this purpose, so in the present study a new self rating scale was used in order to determine whether this was still present and compare the current attitudes to somatic diagnoses and substance misuse with these findings.…”
Section: Discussionmentioning
confidence: 93%
“…The general picture is that people who harm themselves are not popular with health services staff (e.g. Roman, Bancroft,& Skrimshire, 1975; Creed & Pfeffer, 1981; Platt & Salter, 1987; Alston & Robinson, 1992). However, there has been no clear attempt to identify factors that may be influential in staff judgments of patients presenting with deliberate self‐harm.…”
mentioning
confidence: 99%